Peran Kualitas Tidur terhadap Psychological Distress pada Remaja - Walidah, Azka; Syakarofath, Nandy Agustin (Fakultas Psikologi, Universitas Islam Negeri Raden Fatah Palembang, Sumatra Selatan, 2025)
Adolescence as a developmental transition between childhood and adulthood. In adolescents, it often causes increased psychological distress. In fact, healthy adolescent development is crucial for long-term consequences. Thus, it is necessary to pay attention to one of the factors that can influence psychological distress in adolescents, namely sleep quality. Sleep quality showed stronger associations with all measures of emotion. The aim of this research is to determine the role of sleep quality on psychological distress in adolescents. This study used a simple linear regression method with subjects aged 12 - 21 years. The instruments used were the Pittsburgh Sleep Quality Index Indonesian and the Indonesian Mental Health Inventory-38 which were then analyzed using Jamovi 2.3.28 software. The research results show that sleep quality can predict psychological distress in adolescents. The role of sleep quality in predicting psychological distress is 27.8% in a positive direction. The sleep quality aspect is reviewed from seven aspects with the order of greatest prediction, namely daytime dysfunction, subjective sleep quality, sleep disturbance, sleep latency, use of sleeping medication, sleep duration, and sleep efficiency. The mechanism of sleep quality is able to predict psychological distress related to decreased brain function performance. Thus, the conclusion obtained is that sleep quality plays a role in predicting psychological distress in adolescents. The combination of a number of aspects makes sleep quality vulnerable to psychological distress. Implications of this research will increase insight and understanding of interventions on the importance of quality sleep in the long term.